ANALISIS BIAYA, VOLUME, DAN LABA PADA USAHA PENGGILINGAN IKAN TENGGIRI DI KOTA BENGKULU (STUDI KASUS HOME INDUSTRY BINTANG LAUT) - Chairunissa, Nurul; Reswita, Reswita; Irnad, Irnad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Research aims to calculate income, the break event point, profitability, and sensitivity at a venture grinding fish Bintang Laut. Analysis methods used was a qualitative methodology .Value analysis of income business sector was Rp 10.312.343,17. Break event point a is 18,84 kilogram or Rp 1.876.116,65. And value for profitability is 17 % and value for sensitivity is Rp 1,03. Based on the research, can be concluded that this business advantageous and can increase profit by means of increase production and boost sales.